Application of mucous membrane dermoscopy (mucoscopy) in diagnostics of benign oral lesions ‐ literature review and preliminary observations from International Dermoscopy Society study. Issue 1 (18th November 2020) - Kumar Jha, Abhijeet; Vinay, Keshavamurthy; Sławińska, Martyna; Sonthalia, Sidharth; Sobjanek, Michał; Kamińska‐Winciorek, Grazyna; Errichetti, Enzo; Kamat, Divya; Chatterjee, Debajyoti; Apalla, Zoe; Zalaudek, Iris; Goldust, Mohamad; et al.
Abstract: Dermoscopy of mucosal surface termed "mucoscopy" is an upcoming offshoot of dermatological imaging. However, the literature on mucoscopy is limited to individual cases and small case series. An organized review or systematic analysis of mucoscopy is lacking. The aim of this review was to summarize the published literature on mucoscopic features of benign conditions affecting the oral mucosa and semi‐mucosa. Additionally, the results of mucoscopic features of diseases, which have not been described before have been presented.